TPACK confidence of pre-service teachers in Universiti Utara Malaysia - Raman, Arumugam (MCSER Publishing, Rome-Italy, 2014)
The role of technology in education is undeniable (Niess, 2005).Teachers as moulders of human beings need to be skillful in integrating technology in education to deliver what they teach effectively.According to Malaysian Education Blueprint (2012) pre-service service teachers of Universiti Utara Malaysia are expected to master Information and Communication Technology (ICT) integration in the teaching and learning process (MOE, 2013).This study measures the level of Technological Pedagogical Content Knowledge (TPACK) outlined by Mishra and Koehler (2006).It includes seven knowledge dimensions, namely Content Knowledge (CK), Pedagogical Knowledge (PK), Technological Knowledge (TK), Pedagogical Content Knowledge (PCK), Technological Pedagogical Knowledge (TPK), Technological Content Knowledge (TCK), Pedagogical Content Knowledge (PCK) and Technological Pedagogical Content Knowledge (TPACK).This study involved 154 pre-service teachers from various programs such as a Bachelor's Degree in Education Majoring in Information Technology, Moral Education, Accounting and Business Management.Questionnaire forms were sent through a ‘Google Form’ to their respective emails and responses were analyzed using SPSS software.The findings showed that the pre-service teachers have a high level of competency, confidence and lastly TPACK.The test results have also shown that there is a significant difference between the male and female pre-service teachers regarding the confidence level in using ICT in teaching and learning as revealed by MANOVA analysis.